2017
DOI: 10.2147/copd.s139896
|View full text |Cite
|
Sign up to set email alerts
|

COPD depicted – patients drawing their lungs

Abstract: BackgroundGiven the increasing importance of patient-reported outcomes (PRO) in quality medical care, we examined the value and feasibility of an innovative method for assessing patients’ illness perceptions, represented in drawings made by patients with COPD of their lungs.AimThe aim of our study was: to study patients’ representation of COPD as reflected in their drawings of their lungs; and to examine scores on a validated measure that assesses illness perceptions (ie, Brief Illness Perception Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…With respect to the physical change, the researcher (AV) observed that patients’ drawings depicted more extreme hair loss than expected, when seeing the amount of hair during the personal meeting with the patient. This was also observed in other drawing studies, notwithstanding the fact that hair loss is visible to the patient, rather than the invisible lung or heart damage or disturbed blood cells (sickle cell disease and thalassemia) (Broadbent et al, 2009; Hoogerwerf et al, 2012; Kaptein et al, 2017; Nowicka-Sauer, 2007; Ramondt et al, 2016). In the literature, drawing size is frequently associated with illness perceptions and therefore the experienced severity and impact.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…With respect to the physical change, the researcher (AV) observed that patients’ drawings depicted more extreme hair loss than expected, when seeing the amount of hair during the personal meeting with the patient. This was also observed in other drawing studies, notwithstanding the fact that hair loss is visible to the patient, rather than the invisible lung or heart damage or disturbed blood cells (sickle cell disease and thalassemia) (Broadbent et al, 2009; Hoogerwerf et al, 2012; Kaptein et al, 2017; Nowicka-Sauer, 2007; Ramondt et al, 2016). In the literature, drawing size is frequently associated with illness perceptions and therefore the experienced severity and impact.…”
Section: Discussionsupporting
confidence: 74%
“…Illness perceptions can be distinguished into five domains: identity (illness and symptoms), timeline, consequences, perceived control, and cause. These illness perceptions are frequently obtained using questionnaires such as the Brief-Illness Perception Questionnaire (B-IPQ) (Kaptein et al, 2017). A relatively novel method to assess this perception is the use of drawings as already done in for example, diabetes, sickle cell disease or lung cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular music therapy also helped with management of the anxiety, depression and fatigue that is often associated with the condition (903,904). Studies asking patients to draw their lungs have found that this can highlight any discrepancies between patients' stage of disease and their understanding of their disease (905).…”
Section: Respiratory Diseasementioning
confidence: 99%
“…The department of health clearly pointed out that quitting smoking could prevent and avoid exacerbation of COPD [27]. Kaptein, Tiemensma, Broadbent, Asijee, and Voorhaar [28] tested the feasibility of the innovative approach by asking people with COPD to draw pictures, the picture asked the patient to draw their cognitive lungs, accompanied by a short disease perception questionnaire (Brief-Illness Perception Questionnaire, B-IPQ) to assess patients' awareness of their disease, eighty-seven of them completed the drawing and believed that COPD was related to smoking and truly accepted to quit smoking. Similarly, Wenters and Bygholm [29] browsed COPD patients' communication posts on the site, finding smoking and exercise were the most talked about topics among the 398 patients, who said it was important to change habits and lifestyles and believed that quitting smoking and exercising could prolong their lives.…”
Section: Etiological Preventionmentioning
confidence: 99%